PARAGANGLIOMA OF TRANSVERSE MESOCOLON: A CASE REPORT - Saira Saleem; Amer Sakati (Journal of University Medical & Dental College, 2016)
ABSTRACT Paragangliomas are tumors of neural crest-derived cells that exist along the distribution of autonomic nervous system. Less than 10% of paragangliomas occur in extra-adrenal sites and extend anywhere from the neck to the base of the pelvis. In the abdomen these are symmetrically distributed along the abdominal aorta. Rarely, these occur aberrantly outside this distribution as in this case report. We report a case of 51 year old male with transverse mesocolon paraganglioma, presented at King Fahad Specialist Hospital, Buraidah, Saudi Arabia. It was conﬁrmed histologically and immunohistochemically. Although rare, paraganglioma should be included in the differential diagnosis of solid mesenteric tumours, to prevent any potential life-threatening event peroperatively in the case of a catecholamines-producing tumour.